Hukum Keluarga Islam dalam Perspektif HAM Universal (UDHR) dan HAM Islam (UIDHR) - Muhammad Faisal Hamdani (Universitas Islam Negeri Jakarta, 2016)
Human Rights contain provisions relating to Islamic law, especially family law. As a Sharia scholar, this topic is crucial to observe. This paper analyzes several aspects of family law in human rights, both universal human rights and universal human rights, such as marriage, inheritance, and child custody. There are the similarities and differences in both of these human rights like in the case of marriage. In Universal Declaration Human Rights, marriage is permissible for a couple without consideration of religion at all (article 2), whereas in Universal Declaration Human Rights, there is strong indication (Article 19 (1)a) that inter- religious marriage is forbidden, such as the comments of Elizabeth Mayer and others.DOI: 10.15408/ajis.v16i1.2892